99Tc NMR as a promising technique for structural investigation of biomolecules: theoretical studies on the solvent and thermal effects of phenylbenzothiazole complex. (21st January 2014) - Mancini, Daiana T.; Souza, Eugenio F.; Caetano, Melissa S.; Ramalho, Teodorico C.
<x xml:space="preserve">Abstract</x> The phenylbenzothiazole compounds show antitumor properties and are highly selective. In this paper, the 99Tc chemical shifts based on the (99mTc)(CO)3(NNO) complex conjugated to the antitumor agent 2‐(4′‐aminophenyl)benzothiazole are reported. Thermal and solvent effects were studied computationally by quantum‐chemical methods, using the density functional theory (DFT) (DFT level BPW91/aug‐cc‐pVTZ for the Tc and BPW91/IGLO‐II for the other atoms) to compute the NMR parameters for the complex. We have calculated the 99Tc NMR chemical shifts of the complex in gas phase and solution using different solvation models (polarizable continuum model and explicit solvation). To evaluate the thermal effect, molecular dynamics simulations were carried, using the atom‐centered density matrix propagation method at the DFT level (BP86/LanL2dz). The results highlight that the 99Tc NMR spectroscopy can be a promising technique for structural investigation of biomolecules, at the molecular level, in different environments. Copyright © 2014 John Wiley & Sons, Ltd.